Fear of the COVID-19 Pandemic in Driving Mobile Payment Applications Adoption - Nugroho Hardiyanto; Wahyu Rafdinal; Nono Wibisono; Cahaya Juniarti; Mitha Septiany (Profesional Muda Cendekia Publishing, 2023)
This study aims to analyze how the perceived fear of COVID-19 will affect the adoption of mobile payment applications. The data were collected from 500 mobile payment applications users in Indonesia. The Structural Equation Model-Partial Least Square (PLS-SEM) was used to analyze the relationship between variables and test the hypotheses. According to the findings, perceived fear influences two TAM variables: perceived usefulness and perceived ease of use. Attitude is significantly influenced by the two TAM variables. However, only perceived ease of use has a significant influence on intention to use. Finally, attitude influences the intention to use mobile payment applications. This study will assist mobile payment application providers in planning services and increase the intention of mobile payment applications during the COVID-19 pandemic. This study will also append the subsisting knowledge about the mobile payment applications literature in the context of the pandemic. This research complements the marketing literature in analyzing the adoption of mobile payment applications during the COVID-19 pandemic based on perceived fear of the COVID-19 pandemic.